Research on Cutting Force of Turn-Milling Based on Thin-Walled Blade - Lida Zhu; Baoguang Liu; Xiaobang Wang; Zhiwei Xu (Advances in Materials Science and Engineering)
Turn-milling is regarded as the milling of a curved surface while rotating the workpiece around its center point, which combines effectively the advantages of both turning and milling, wherein it allows for good metal removal with the difficult-to-cut thin-walled workpieces in aviation. The objective of the present work is to study cutting force by turn-milling in cutting condition. Aiming at the deformation properties of thin-walled blade, the predicted models of rigid cutting force and flexible cutting force with ball cutter are provided, respectively, in turn-milling process. The deformation values of blade and cutter are calculated, respectively, based on the engaged trajectory by using the iterative algorithm. The rigid and flexible cutting forces are compared and the influence degrees of cutting parameters on cutting forces are analyzed. These conclusions provide theoretical foundation and reference for turn-milling mechanism research.